Study on Effect of Thermal Cycles on Strength Properties of SCC - S J, Shivaraj; Reddy M S, Shreenivas; P D, Maneeth (International Journal of Engineering and Technology, 2018)
Impact of elevated temperature on the properties of concrete is critical for imperviousness to fire considers. The fire stays a standout amongst the most genuine possibilities unsafe to any building. The effect of sustained temperature on the properties of concrete is important for fire resistance studies. The fire remains one of the most serious potentials hazardous to any building. The main objective of this study was to conduct an exploratory work towards the development of a suitable SCC mix design using local aggregates and to evaluate the performance of the selected SCC mix under thermal variations. Trials mixes using Okamura method of mix design were carried out for the 4 different mix proportions to achieve the final mixes which satisfy all the workability properties. The specimens were cast and cured for 7 & 28 days. Considering the specimens cured for 7 & 28 days as a reference, specimens were subjected to the requisite number of thermal cycles at two different temperatures as 1000C & 1200C. Variation in weight of the specimen after the requisite number of thermal cycles was recorded, then the compressive strength & split tensile strength of thermally treated concrete specimens was determined. The result shows a relative decrease in the strength of thermally treated each specimen as compared to its original strength before heating. The replacement of ordinary Portland cement by mineral admixtures in concrete caused an increase in strength as compared to control mix. The replacements of OPC by Micro Silica have shown the highest strength and fly ash mix shown least strength in this experimental work.Â